Biological nitrogen fixation in field pea and vetch: Response to inoculation and residual effect on maize in the Pampean region - Enrico, Juan Martin; Piccinetti, Carlos Fabian; Barraco, Miriam Raquel; Agosti, Maria Belén; Eclesia, Roxana Paola; Salvagiotti, Fernando (Elsevier, 2020)
Including legumes in winter, both as cover crop or for grain harvest, is recommended for avoiding long periods of bare fallow and supplying N for succeeding crops in the rotation. The aims of this study were to i) quantify the contribution of N derived from biological nitrogen fixation (N_BNF) in vetch (Vicia sativa L. or Vicia villosa L.) and field pea (Pisum sativum) in the Central Pampas region of Argentina, ii) evaluate the response to seed inoculation in terms of %N derived from air (%Ndfa), biomass production and N_BNF in both crops and iii) determine grain yield response to nitrogen fertilization of maize (Zea mays L.) sown after field pea and vetch with and without inoculation. %Ndfa was assessed in 16 experimental sites using the natural 15N abundance method. Response to inoculation in vetch and field pea and the residual effects on the following maize was evaluated during two years. On average, 60 % of N demand of vetch and field pea was met by BNF. Seed inoculation increased %Ndfa in field pea and vetch, and a positive impact on aboveground biomass and N_BFN was observed in vetch. Maize yield did not respond to N fertilization when planted after inoculated vetch, and the largest responses to N fertilization were observed when vetch and field pea were not inoculated. Legume inoculation had a strong impact at the system level, especially in fields that vetch or field pea was not previously cultivated, reducing the economic optimal nitrogen fertilizer rate in the succeeding maize.